Trait and state anxiety in healthcare professionals of intensive care unit - Michele Nunes Fenzke; Wendy Julia Mariano Viante; Bianca Fontana Aguiar; Bárbara da Silva Gama; Adriano Marçal Pimenta; Fernanda Moura D'Almeida Miranda (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To estimate trait and state anxiety levels among intensivecare professionals during the Covid-19 pandemic. Method: Cross-sectional, analytical study, conducted from April to July 2022, in a teaching hospital in southern Brazil, using the State-Trait Anxiety Inventory scale. Results: Trait and state anxiety were present in more than half of the sample, being associated with gender, age group, having children, weekly workload, time working in the hospital and ICU (p<0.05) for the state; and associated with gender, having children, profession, daily and weekly workload, and time working in the hospital (p<0.05) for the trait. Conclusion: Trait and state anxiety were medium to high level for women, young, without children, non-nurses, with a daily shift of 9 to 18 working hours, a weekly workload of more than 40 hours, with less than five years of experience in intensive care and with more than five years of experience working in the institution.